Fever Without a Source in Children Less Than 28 Days, 28 to 90 Days, and 3 to 36 Months - Patrick McVey (Association of American Medical Colleges, 2006)
Abstract This resource is a problem-based learning case designed to teach students about the evaluation of fever without a source (FWS) in young children in the emergency room or clinic setting, including the use of the Rochester Criteria and Philadelphia Protocol. Students are also given the opportunity to apply this information to varying clinical scenarios so that they may better understand the issues of treating neonates versus slightly older children. In addition, following teaching about the initial workup, students are given a chance to consider the rationale behind each of the tests that are commonly ordered so that they might better understand the strength and weakness of each test. Finally, students are presented with a chance to think critically about the common bacterial and viral causes of FWS and what the appropriate antimicrobial intervention should be. By doing this, they are able to take three diverse patients from initial evaluation to disposition and see how all parts are interconnected. This resource may be used as a self-study tool, a small-group facilitated discussion, or an interactive lecture. Medical students often have varying levels of skill in applying clinical knowledge, especially at different times as they progress through their clinical course work. Acknowledging this difference in ability allows the teacher to better adapt the material to students' current skill levels. Establishing a contextual understanding of why, how, and when to treat FWS is something that is often lost in traditional lectures. Providing students with the opportunity to see how this information applies to a real-life situation gives them not only the knowledge they need but a framework in which it can be used.